Studi Laboratorium Penentuan Pour point dan Cold point Pada Crude oil Sumur AS-198, AS-211, AS-217, dan AS-219 - Junaya, Indah Asa Ujun; Rivani, Mukhlis Farhan; Wahyuni, Viola Sri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Crude oil with a high wax content often causes flow problems, especially at low temperatures, which can cause the fluid to thicken to the point where it cannot flow. This condition has the potential to disrupt oil production and transportation processes in the field. Therefore, an analysis of fluid characteristics through pour point and cold point testing is required to determine safe operating temperature limits. This study was conducted using laboratory testing methods on crude oil samples from wells AS-198, AS-211, AS-217, and AS-219 in the Sangatta Field. The testing involved a gradual cooling process until the fluid lost its flowability. The test results indicate that each sample exhibits distinct characteristics, influenced by fluid composition and heavy hydrocarbon content. As wax content increases, the tendency for the pour point to rise also increases, thereby elevating the risk of flow disruption. Consequently, management methods such as heating or the use of chemicals are required to maintain flow stability during the production process.